Ultrastructure of the ducts of the reproductive tract of males of Melipona bicolor bicolor Lepeletier (Hymenoptera, Apinae, Meliponini) - Dallacqua, R. P.; da Cruz-Landim, C. (Blackwell Verlag Gmbh, 2003)
The present paper describes the ultrastructural features of seminal vesicle, post-vesicular vas deferens and ejaculatory duct of Melipona bicolor bicolor from newly emerged and mature males. Although the results do not show very consistent morphological signs of secretory activity by the epithelium of these organs, lipidic droplets and lamellar granules present in mature males' seminal vesicles and the vacuoles present in post-vesicular vas deferens are probably secretion. Besides, the spermatozoa in the lumen are immersed in a material of characteristic structure, which must be produced in superior regions of the reproductive system of immature males, not studied here. The presence of sperm cells, apparently in cytoplasm vesicles of seminal vesicle and post-vesicular vas deferens, suggests spermiophagy by their epithelium.